Banana production under the fair-trade system: an analysis of the Ecuadorian case - Borja, Juan (2016)
This work analyzes banana fair-trade in Ecuador. By means of this system, organized small-scale farmers were able to improve their earning compared to those involved in traditional trade. Additionally, fair-trade is also associated with a reduction in the application of inputs and the use of cleaner technologies which have a lower environmental impact. The potential and limitations of the fair-trade system is also discussed throughout the text.